Rancang Bangun Media Bahan Ajar Digital Berbasis Multimodalality Dalam Pendekatan Pedagogik Futuristik - Hana Yunansah; Yeni Yuniarti; Yusuf Tri Herlambang; Rahman Wahid; Ani Hendriyani (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
This study aims to describe the Design of digital Media teaching materials based multimodality approach to pedagogic futuristic. The research method used is the method of Design and Development using model 4-D. Data collection techniques used were questionnaires and interviews. The research results found showed that the medium of digital teaching materials that has been developed is feasible to use based on the assessment of the experts to obtain the percentage of 97.5% in terms of material, for 82.5% in terms of the media, and 100% in terms of language. Summary assessment of teaching materials by students earn a percentage 96,87% in terms of the content of the material, 100% in terms of use, and 100% in terms of appearance.